John D.M. Hamilton papers - Hamilton, John D. M., 1892-1973.
Correspondence, speeches, interviews, subject files, and other papers relating primarily to Hamilton's career in the Republican Party, including his years as chairman of the Republican National Committee. Subjects include the Republican national conventions of 1936 and 1940; presidential campaigns of 1940, 1944, and 1952; and congressional elections in 1938. Individuals represented include Herbert Hoover, Alfred M. Landon, Douglas MacArthur, Charles Linza McNary, Robert A. Taft, William Allen White, and Wendell L. Willkie.
Microfilm edition only available of "The Republican strategy in the campaigns of 1936 and 1940" by Henry O. Evjen (Ph.D. dissertation, Western Reserve University, 1950)
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Lawyer, state legislator, and public official of Kansas. Full name: John Daniel Miller Hamilton.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hoover, Herbert, -- 1874-1964.; Landon, Alfred M. -- 1887-1987.; MacArthur, Douglas, -- 1880-1964.; McNary, Charles Linza, -- 1874-1944.; Taft, Robert A. -- 1889-1953.; Willkie, Wendell L. -- 1892-1944.; White, William Allen, -- 1868-1944.; United States. -- Congress -- Elections; Republican National Committee (U.S.); Republican Party (U.S. : 1854- ); Political conventions -- United States; Presidents -- United States -- Election -- 1936.; Presidents -- United States -- Election -- 1940.; Presidents -- United States -- Election -- 1944.; Presidents -- United States -- Election -- 1952.; United States -- Politics and government -- 20th century; Lawyers; Legislators -- Kansas; Public officials -- Kansas